Chapter Les réseaux négociants européens et les échanges entre la France et l'Europe du Nord (XVIIe-XIXe siècles) - Pourchasse, Pierrick (Atti delle «Settimane di Studi» e altri Convegni, 2019)
France was a country that had great agricultural potential and natural resources that allowed it to not be dependent on external markets, especially raw materials from the North. French ports, however, maintained close relations with the Baltic countries where they marketed many products and obtained supplies of naval stores and, depending on the economic situation, cereals. This paper proposes to revisit the French trade with the Baltic over a period of two centuries by using the Sound Toll Accounts whose entire data is now available to the research community. As we will see, several evidences are to be reconsidered.